PACA 2015: ações frente à causa ambiental - Scatena, Raphaela Sepulveda [UNESP]; Buzutti, Paula Carolina [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The PACA - Active posture towards the Environmental Cause is an extension group focused on environmental education and awareness that aims to carry out projects and events that bring both the internal UNESP community , as the external, environmental issues, aiming to motivate changes in peoples habits, generating susteinable actions. This way, the group promotes activities at the university like collecting used oil, batteries, among others. In the year of 2015 we had a significant increase in membership, which helped us to have new ideas and realize partnership with other groups in an attempt to overcome the declining interest of students in extra curricular activities.

O PACA – Postura Ativa Frente à Causa Ambiental é um grupo de extensão voltado para a educação e conscientização ambiental e tem por objetivo realizar projetos e eventos que aproximem tanto a comunidade interna a UNESP, quanto a externa, as questões ambientais, visando motivar mudanças nos hábitos das pessoas, gerando ações sustentávies. Dessa forma, o grupo realiza atividades na universidade como coleta de óleo usado, coleta de pilhas, entre outras. No ano de 2015 tivemos um aumento importante no número de membros, o que nos ajudou a ter novas ideias e realizar parceria com outros grupos, na tentativa de superar o crescente desinteresse dos universitários em atividades extra curriculares.
Keywords: Environment; Sustainability; Project; Meio ambiente; Sustentabilidade; Projeto